Photoactivation of bone marrow mesenchymal stromal cells with diode laser: Effects and mechanisms of action1. Issue 1 (4th October 2012) - Giannelli, Marco; Chellini, Flaminia; Sassoli, Chiara; Francini, Fabio; Pini, Alessandro; Squecco, Roberta; Nosi, Daniele; Bani, Daniele; Zecchi‐Orlandini, Sandra; Formigli, Lucia
Abstract Mesenchymal stromal cells (MSCs) are a promising cell candidate in tissue engineering and regenerative medicine. Their proliferative potential can be increased by low‐level laser irradiation (LLLI), but the mechanisms involved remain to be clarified. With the aim of expanding the therapeutic application of LLLI to MSC therapy, in the present study we investigated the effects of 635 nm diode laser on mouse MSC proliferation and investigated the underlying cellular and molecular mechanisms, focusing the attention on the effects of laser irradiation on Notch‐1 signal activation and membrane ion channel modulation. It was found that MSC proliferation was significantly enhanced after laser irradiation, as judged by time lapse videomicroscopy and EdU incorporation. This phenomenon was associated with the up‐regulation and activation of Notch‐1 pathway, and with increased membrane conductance through voltage‐gated K+, BK and Kir, channels and T‐ and L‐type Ca2+ channels. We also showed that MSC proliferation was mainly dependent on Kir channel activity, on the basis that the cell growth and Notch‐1 up‐regulation were severely decreased by the pre‐treatment with the channel inhibitor Ba2+ (0.5 mM). Interestingly, the channel inhibition was also able to attenuate the stimulatory effects of diode laser on MSCs, thus providing novel evidence to expand our knowledge on the mechanisms of biostimulation after LLLI. In conclusions, our findings suggest that diode laser may be a valid approach for the preconditioning of MSCs in vitro prior cell transplantation. J. Cell. Physiol. 228: 172–181, 2013. © 2012 Wiley Periodicals, Inc.